Shells in CO2 clusters. Issue 9 (22nd February 2022) - Niman, John W.; Kamerin, Benjamin S.; Kresin, Vitaly V.; Krohn, Jan; Signorell, Ruth; Halonen, Roope; Hansen, Klavs
Abstract : A rich set of abundance spectra of CO2 clusters is analyzed within the evaporative ensemble framework, revealing strikingly universal stability patterns. Cluster dissociation energies and packing structures are deduced and discussed in detail. Abstract : Abundance spectra of (CO2 ) N clusters up to N ≈ 500 acquired under a wide range of adiabatic expansion conditions are analyzed within the evaporative ensemble framework. The analysis reveals that the cluster stability functions display a strikingly universal pattern for all expansion conditions. These patterns reflect the inherent properties of individual clusters. From this analysis the size-dependent cluster binding energies are determined, shell and subshell closing sizes are identified, and cuboctahedral packing ordering for sizes above N ≈ 130 is confirmed. It is demonstrated that a few percent variation in the dissociation energies translates into significant abundance variations, especially for the larger clusters.